Performan produksi sapi peranakan fries holland jantan yang dipelihara pada macam pakan penggemukan yang berbeda - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1993)
The feedlot (fattening) has been recognized as a method for improving beef cattle production including carcass quality. This experiment was conducted to study the growth rate, feed consumption and conversion, and carcass production of male Holstein-Friesian grade was fattened under three different diets of two consetrates (CI, CH) and roughages (king grass, corn silage). The male Holstein-Friesian grade consisting of 16 grower (group I) and 12 finisher cattle (group II), were fattened with four different treatment diets the combination of 70% CI and 30% king grass (A)